2005
DOI: 10.1007/s10522-004-7379-6
|View full text |Cite
|
Sign up to set email alerts
|

The stationary phase model of aging in yeast for the study of oxidative stress and age-related neurodegeneration

Abstract: Understanding the biochemical and genetic alterations that occur during the aging of post-mitotic cells is critical for understanding the etiology of abnormalities observed during the aging of the central nervous system (CNS). While many theories for cellular aging exist, the free radical theory of aging has proved useful in explaining multiple aspects of post-mitotic cell aging, including the aging of neuronal cells. It is well established that Saccharomyces cerevisiae are an invaluable model system for explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
57
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 54 publications
(193 reference statements)
3
57
0
Order By: Relevance
“…Wild-type cells that are grown in synthetic complete minimal medium lose viability after 10 d (our unpublished observations). In contrast, cells that are grown and maintained in stationary phase on rich media can maintain viability for weeks (Sinclair et al, 1998;Chen et al, 2005). We found that there was a rapid decline in the viability of our oye2⌬ cells compared with wild-type cells (Figure 4).…”
Section: C374amentioning
confidence: 82%
“…Wild-type cells that are grown in synthetic complete minimal medium lose viability after 10 d (our unpublished observations). In contrast, cells that are grown and maintained in stationary phase on rich media can maintain viability for weeks (Sinclair et al, 1998;Chen et al, 2005). We found that there was a rapid decline in the viability of our oye2⌬ cells compared with wild-type cells (Figure 4).…”
Section: C374amentioning
confidence: 82%
“…Strikingly, many of the key aspects of yeast aging closely resemble those of mammalian cells, especially postmitotic neurons (for example oxidative stress, decreased proteasome function and the accumulation of somatic mutations) [134][135][136] . The biology of postmitotic cells is profoundly different than that of dividing cells and since in almost all of these diseases it is predominantly postmitotic neurons that are affected, examining yeast models of neurodegenerative disease in the context of nondividing aged cells will be crucial, and perhaps much more directly relevant to the biology of aging neurons [137] . There are 2 types of aging models in yeast: replicative and chronological [138,139] .…”
Section: The Effect Of Aging On Yeast Neurodegenerative Disease Modelsmentioning
confidence: 99%
“…Recent studies have demonstrated that yeast are a useful model with which to study ␣-synuclein toxicity (17)(18)(19), with the previous studies in mitotic yeast contributing to our understanding of what cellular processes are likely important in promoting and inhibiting ␣-synuclein toxicity. Numerous studies have demonstrated that yeast are also useful in studying the biochemistry and regulation of aging in both mitotic and post-mitotic cells (20 -22).…”
mentioning
confidence: 99%